AN APPROACH FOR RAILWAY PROJECT MANAGEMENT - Zafirovski Zlatko; Nedevska Ivona; Gacevski Vasko; Ristov Riste; Ognjenovic Slobodan; Lazarevska Marijana; Kostadinovski Saso (Department of Civil Engineering and Geodesy, Faculty of Technical Sciences, Novi Sad, 2023)
This paper aims to solve this problem, which has recently become more common in railway projects. The key is in a planned approach and organization from the beginning of the project, which the candidate considers by elaborating a Methodology for the construction of the site in the form of a document. This methodology solves all the above and helps lead the project from its beginning to the end with a positive result. The scope of the methodology for the construction of a facility includes several scientific disciplines directly related to the realization of the facility, such as law, economics, ecology, quality management, construction, etc. Therefore, it should cover all matters in these areas and provide solutions and courses of action at the beginning and in the development phase of the site to adapt to possible needs and to be finalized. The conclusion is that the application of such a Methodology for the construction of the site is necessary, or it could be freely said that it is mandatory.
Keywords: methodology, fidic, railway projects, quality management